When patrons are not patrons: A social-scientific reading of the rich man and Lazarus (Lk 16:19–26) - Eck, Ernest Van (HTS teologiese studies, 2009)
This article presents a social-scientific interpretation of the parable of the rich man and Lazarus. Attention is first given to the history of the interpretation of the parable and to the integrity and authenticity of this interpretation. A social-scientific reading of the parable is then presented in terms of the strategy and the situation of the parable. In terms of the latter, the parable is read against the backdrop of an advanced agrarian (aristocratic) society in which patronage and clientism played an important role. Regarding the parable’s strategy, it is argued that the different oppositions in the parable serve to highlight their only similarity: those who have the ability to help do not help. The gist of the parable is that patrons who do not act like patrons create a society wherein a chasm so great between rich and poor is brought into existence that it cannot be crossed.